Monitoring of Early Changes of Circulating Tumor DNA in the Plasma of Rectal Cancer Patients Receiving Neoadjuvant Concomitant Chemoradiotherapy: Evaluation for Prognosis and Prediction of Therapeutic Response - Pazdirek, Filip; Minarik, Marek; Benesova, Lucie; Halkova, Tereza; Belsanova, Barbora; Macek, Milan; Stepanek, Lubomír; Hoch, Jiri (Frontiers in Oncology, 2020)
Introduction: Patients with locally advanced rectal cancer (LARC) are undergoing neoadjuvant chemoradiotherapy (NCRT) prior to surgery. While in some patients the NCRT is known to prevent local recurrence, it is also accompanied by side effects. Accordingly, there is an unmet need to identify predictive markers allowing to identify non-responders to avoid its adverse effects. We monitored circulating tumor DNA (ctDNA) as a potential liquid-biopsy based biomarker. We have investigated ctDNA changes plasma during the early days of NCRT and its relationship to the overall therapy outcome. Methods and Patients: The studied cohort included 36 LARC patients (Stage II or III) undergoing NCRT with subsequent surgical treatment. We have detected somatic mutations in tissue biopsies taken during endoscopic examination prior to the therapy. CtDNA was extracted from patient plasma samples prior to therapy and at the end of the first week. In order to optimize the analytical costs of liquid-biopsy testing, we have utilized a two-level approach in which first a low-cost detection method of denaturing capillary electrophoresis was used followed by examination of initially negative samples by a high-sensitivity BEAMING assay. The ctDNA was related to clinical parameters including tumor regression grade (TRG) and TNM tumor staging. Results: We have detected a somatic mutation in 33 out of 36 patients (91.7 %). 7 patients (7/33, 21.2 %) had ctDNA present prior to therapy. The ctDNA-positivity before treatment reduced postoperative disease free survival and overall survival by an average of 1.47 years, and 1.41 years, respectively (p = 0.015, and p = 0.010). In all patients ctDNA was strongly reduced or completely eliminated from plasma by the end of the first week of NCRT with no correlation to any of the parameters analyzed. Conclusions: The baseline ctDNA presence represented a statistically significant negative prognostic biomarker for the overall patient survival. As ctDNA was reduced indiscriminately from circulation of all patients, dynamics during the first week of NCRT it is not suited for predicting the outcome LARC. However, the general effect of rapid ctDNA disappearance apparently occurring during the initial days of NCRT is noteworthy and should further be studied.